Histone demethylase KDM5C is a SAHA-sensitive central hub at the crossroads of transcriptional axes involved in multiple neurodevelopmental disorders. (6th November 2019) - Poeta, Loredana; Padula, Agnese; Attianese, Benedetta; Valentino, Mariaelena; Verrillo, Lucia; Filosa, Stefania; Shoubridge, Cheryl; Barra, Adriano; Schwartz, Charles E; Christensen, Jesper; van Bokhoven, Hans; Helin, Kristian; et al.
Abstract: A disproportional large number of neurodevelopmental disorders (NDDs) is caused by variants in genes encoding transcription factors and chromatin modifiers. However, the functional interactions between the corresponding proteins are only partly known. Here, we show that KDM5C, encoding a H3K4 demethylase, is at the intersection of transcriptional axes under the control of three regulatory proteins ARX, ZNF711 and PHF8. Interestingly, mutations in all four genes ( KDM5C, ARX, ZNF711 and PHF8 ) are associated with X-linked NDDs comprising intellectual disability as a core feature. in vitro analysis of the KDM5C promoter revealed that ARX and ZNF711 function as antagonist transcription factors that activate KDM5C expression and compete for the recruitment of PHF8. Functional analysis of mutations in these genes showed a correlation between phenotype severity and the reduction in KDM5C transcriptional activity. The KDM5C decrease was associated with a lack of repression of downstream target genes Scn2a, Syn1 and Bdnf in the embryonic brain of Arx -null mice. Aiming to correct the faulty expression of KDM5C, we studied the effect of the FDA-approved histone deacetylase inhibitor suberanilohydroxamic acid (SAHA) . In Arx -KO murine ES-derived neurons, SAHA was able to rescue KDM5C depletion, recover H3K4me3 signalling and improve neuronal differentiation. Indeed, in ARX/alr-1- deficient Caenorhabditis elegans animals, SAHA was shown to counteract the defective KDM5C/rbr-2- H3K4me3 signalling, recover abnormal behavioural phenotype and ameliorate neuronal maturation. Overall, our studies indicate that KDM5C is a conserved and druggable effector molecule across a number of NDDs for whom the use of SAHA may be considered a potential therapeutic strategy.